Potential new treatment for non-freezing cold injury: is Iloprost the way forward?. Issue 5 (23rd March 2017) - Ionescu, Anne-Marie; Hutchinson, Sarah; Ahmad, Mehtab; Imray, Christopher
Abstract : Introduction: Non-freezing cold injury (NFCI) remains largely under-reported, and is of particular importance in the armed forces where its prevalence is greatest. Iloprost, a synthetic prostaglandin I2 analogue, has previously been used with some success in the treatment of vasospastic and freezing cold injuries, although its role in NFCI remains unclear. Case report: An Iloprost infusion was used to treat the long-term sequelae of an ex-soldier suffering with ongoing pedal pain and loss of function 20 years after the initial NFCI insult sustained on military exercise. Following 5 days of iloprost infusion, he reported 4 weeks of markedly reduced pain and increased mobility before symptom relapse. A second infusion was thus given 3 months later, which resulted in increased pain and analgesic requirements. Discussion: The use of iloprost in the treatment of NFCI is discussed and its use in a condition which physicians consistently struggle to treat effectively is considered. Careful counselling is recommended as symptoms may be worsened.